Uganda : Report on Observance of Standards and Codes-Fiscal Transparency Module-Update. (IMF Staff Country Reports; Country Report ;, 2003)
This paper presents an update to the Report on the Observance of Standards and Codes (ROSC) on Fiscal Transparency for Uganda. Since the 1999 ROSC, Uganda has made significant progress in enhancing transparency practices in the fiscal area. They have inter alia divested public enterprises, thereby reducing the scope for conducting off-budget quasi-fiscal operations. The authorities have compiled statistics of line ministries' revenue, bringing this revenue under the control of the Treasury, and have extended the budgeting framework to cover district and local government budget processes.